2013
DOI: 10.1111/php.12176
|View full text |Cite
|
Sign up to set email alerts
|

Amplified Production of Singlet Oxygen in Aqueous Solution Using Metal Enhancement Effects

Abstract: Studies involving metal enhancement effects have gained popularity, and enhancement of fluorescence due to the close proximity of a dye molecule to a metal nanoparticle is well documented. Although enhancement of singlet oxygen production by metal has been reported, studies are relatively scarce and so far only stationary silver island films have been proven to be adequate to do so. Herein, we describe the synthesis and characterization of core-shell nanoparticles on which a photosensitizer acting as source of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
29
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(30 citation statements)
references
References 70 publications
1
29
0
Order By: Relevance
“…Most photosensitizers (PSs) are highly hydrophobic and require delivery systems. It was showed that GNPs can enhance singlet oxygen generation or photodynamic therapy efficiency of different photosensitizers [23][24][25], which may be due to localized surface plasmon resonance (LSPR) of the metal nanoparticles according to most of the scientists [26,27]. However, our group demonstrated that the cancer cell killing enhancement is mainly due to GNPs' efficient drug delivery [28].…”
Section: Introductionmentioning
confidence: 83%
“…Most photosensitizers (PSs) are highly hydrophobic and require delivery systems. It was showed that GNPs can enhance singlet oxygen generation or photodynamic therapy efficiency of different photosensitizers [23][24][25], which may be due to localized surface plasmon resonance (LSPR) of the metal nanoparticles according to most of the scientists [26,27]. However, our group demonstrated that the cancer cell killing enhancement is mainly due to GNPs' efficient drug delivery [28].…”
Section: Introductionmentioning
confidence: 83%
“…Direct catalytic oxidationo fT MB by molecularo xygen is analogous to the oxidasea ctivity.C urrently,f ew oxidasee nzymes are used in ELISAa ssays.C ompared with some reported oxidasem imics (e.g.,C eO 2 nanoparticles [12] ), photosensitizers are advantageous in terms of their reproducibility,s tructural tunability, [13] andm uch smaller size.…”
Section: Photosensitizers As Amolecular Enzyme Mimicmentioning
confidence: 99%
“…Using this strategy, our group recently reported the synthesis of new multilayer core-shell Ag-silica MNPs onto which a photosensitizer was covalently attached. [138] In our study, a silica shell thickness of about 22 nm afforded the optimal separation between the Ag-core MNPS (68 nm) and the photosensitizer, Rose Bengal. [138] These new MNPs lead to the highest 1 O 2 enhancement factor (ca.…”
Section: Metallic Nanoparticles As Photosensitizer Carriersmentioning
confidence: 99%
“…[138] In our study, a silica shell thickness of about 22 nm afforded the optimal separation between the Ag-core MNPS (68 nm) and the photosensitizer, Rose Bengal. [138] These new MNPs lead to the highest 1 O 2 enhancement factor (ca. 4) ever reported for MNP-photosensitizer systems.…”
Section: Metallic Nanoparticles As Photosensitizer Carriersmentioning
confidence: 99%